Magnetoresistance study of (La0.67Sr0.33MnO3)1-x(NiO)x composite - Zarina Hussain.
This project is to study the influence of NiO adding in (La0.67Sr0.33MnO3)1-x (NiO)x where x is set at 0.00, 0.05, 0.10, 0.15 and 0.20. The samples were prepared via solid state reaction. The sample of magnetoresistance, structure, surface morphology and magnetic properties were investigated using four point probe system, X-ray diffraction (XRD), Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDX). The XRD analysis show that all samples are in single phase with distorted perovskite rhombohedral structure from the John Teller distortion. SEM microanalysis shows that samples give clearer grain size, grain boundary, and porosity for small additional of NiO in LSMO, it gets almost clearer grain boundary. But when increase number of doping it get blur grain. No clear pores can be observed and the samples are compact. EDX analysis indicate that as x increases, more and more, Ni diffuses from the interior of the LSMO grains and gets segregated in the grain boundaries. On the other hand, negative CMR value obtained in all sample imply that the drop of resistance under the influence of the external magnetic field. Low Field Magnetoresistance (LFMR) is observed in all samples and the effect is stronger for smaller grain sizes distribution. This concluded that grain sizes influence LFMR where the smaller grain sizes gives larger LFMR effect.